Revisit Intention in Rural Tourism: The Roles of Service Quality, Facilities, and Accessibility - Kusuma, Gede Yogananta Surya; Puspaningrum, Astrid (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Revisit Intention is a form of tourist loyalty, and loyalty is an important indicator of success in the development of tourism destinations that can have a long-term impact. Service quality is the level of service excellence provided to tourists so as to influence the intention to visit again. Tourist facilities make it easier to serve tourist activities or activities so as to encourage tourists' intention to visit again. Accessibility determines whether or not the location is easy for tourists to reach, thus influencing the intention to visit again. This study aims to analyze and explain the effect of service quality, facilities, and accessibility on the revisit intention of visitors to Penglipuran Tourism Village in Bangli Regency. This type of research is explanatory research. The sampling technique used in this study was non-probability sampling using purposive sampling method. The population in this study were tourists of Penglipuran Tourism Village and a sample of 160 respondents was obtained with the criteria that respondents were at least 17 years old and had visited Penglipuran Tourism Village. This study uses multiple linear analysis and the results show that facilities and accessibility have a significant influence on revisit intention, but service quality has no effect on revisit intention.